2004
DOI: 10.1177/030802260406700802
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Use of Videogames within Secure Forensic Settings: A Review of the Literature and Application to Practice

Abstract: Citation: Gooch, P. & Living, R. (2004). The therapeutic use of videogames within secure forensic settings: a review of the literature and application to practice. The British Journal of Occupational Therapy, 67(8), This is the draft version of the paper.This version of the publication may differ from the final published version. Permanent repository link: Introduction Occupational therapy and leisureIn a newly revised definition of occupational therapy, the College of Occupational Therapists has noted:The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…All participants were able to explore the gaming environment, regardless of previous gaming or computer experience. The observation that all participants engaged actively in the game play and stated that they enjoyed doing so is an important finding as the FMH client group is often characterized as low in volition and engagement (Gooch & Living ). The collaboration between mental health professionals, game designers and service users in creating the gaming environment appeared to allow for a realistic and enjoyable gaming experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were able to explore the gaming environment, regardless of previous gaming or computer experience. The observation that all participants engaged actively in the game play and stated that they enjoyed doing so is an important finding as the FMH client group is often characterized as low in volition and engagement (Gooch & Living ). The collaboration between mental health professionals, game designers and service users in creating the gaming environment appeared to allow for a realistic and enjoyable gaming experience.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that serious games are also applicable in FMH services. Gooch & Living () used video games in forensic settings and concluded that exploration in manipulated environments helps FMH service users develop coping skills. According to Stone (), simulations/virtual worlds enable challenging or hazardous tasks to be practiced in safe, cost‐effective environments, although transferable skill development is dependent on the level of real‐world fidelity.…”
Section: Serious Gamesmentioning
confidence: 99%
“…Physical skills may refer to ability or fast reactions, whereas mental ones concern logic thinking and strategy as well as trivia knowledge (Gooch & Living, 2004). Graphic-adventures can also include tasks that are more typically used in other genres of videogames.…”
Section: E Games Of Skill / Abilitymentioning
confidence: 99%
“…The literature provides evidence to support the efficacy of occupational therapy interventions focused on life skills training, social participation, education, work, and health and wellness (Bond, Drake, & Becker, 2008;Dilk & Bond, 1996;Dunn, Trivedi, Kampert, Clark, & Chambliss, 2005;Granholm et al, 2005;Gutman et al, 2007). Several studies have demonstrated that participation in meaningful occupations promotes health and wellness among individuals experiencing severe mental illness (Gooch & Living, 2004;Haertl & Minato, 2006;Mee, Sumsion, & Craik, 2004). Further, intensive interventions addressing clientcentered, occupation based skills training can foster individuals living with mental illness to fully engage in the world around them (Champagne & Gray, 2011).…”
Section: Introductionmentioning
confidence: 99%